Effect of transactional analysis intervention on parent-adolescent conflict, emotional regulation, and depression among adolescents in Bangladesh - Tasmina, Tanni Khandaker (2022)
Transactional Analysis (TA) by Eric Berne focused on the paradigm of the parent, adult, and child ego states. TA therapy tools have successfully reduced conflicts between parents and adolescents, emotional regulation, and depression. The main objective of this study is to examine the effect of transactional analysis intervention on parent-adolescent conflict, depression, and emotional regulation. This research used an experimental design. This study was carried out using a non-equivalent pre-and post-test design.60 students were randomly allocated to one of two groups: experimental (TA Intervention) or control (non-TA Intervention). Pre- and post-test trails were used to determine the scores of the dependent variables. A pre-test was administered to all study participants to assess the level of parental-adolescent conflict, emotional control, and depression. After the twelve sessions, their levels of parent-adolescent conflict, emotional regulation, and depression were tested again to see if the transactional Analysis intervention influenced the level of dependent variables. Instrumentations used are Conflict Behavior Questionnaire short form (1984), Emotion Regulation Questionnaire (2003), and Beck Depression Inventory BDI. The descriptive analysis was performed to describe the participants' demographic profile, including their age, gender, grade of education, and parental marital status. The independent sample t-test was used to evaluate the mean scores of parent-adolescent conflict, emotional Regulation, and depression between the experimental and control groups' post-test findings. A significant difference was detected between the groups. The paired sample t-test was used to compare the mean scores of the pre-test and post-test results of parent-adolescent conflict, emotional regulation, and depression between the experimental and control groups, and there was a significant difference in the mean scores. The MANOVA was used to determine the considerable effect of groups and genders on Parent-adolescent conflict, emotional regulation, and depression. The findings demonstrated that Transactional Analysis was more successful for adolescents dealing with parent-adolescent conflict, emotional regulation, and depression in the experimental group than in the control group subjects. Transactional analysis therapy's therapeutic tools were found to be successful in improving parent-adolescent conflict, functional emotional control, and assisting in the resolution of depressive symptoms. The current study is a pioneer experimental investigation in Bangladesh to determine the effect of TA on parent-adolescent conflict, emotional control, and depression, which will assist mental health professionals in better treating adolescent conflict, emotional regulatory strategies, and depression in Bangladeshi adolescents.